"COGITOR ERGO SUM": ON THE MEANING AND RELEVANCE OF BAADER's THEOLOGICAL CRITIQUE OF DESCARTES - Geldhof, Joris (Modern theology, 2005)
This paper examines the arguments on the basis of which Franz Baader (1765-1841), the almost forgotten contemporary of Hegel and Schelling, rejected Descartes’ philosophy so decisively, that, at the end of his life, he wrote to a friend that he passionately wanted to put an end to Cartesianism. I defend the thesis that Baader's hostility to Cartesianism was ultimately grounded in a theological idea, and that his holistic and emphatically Christian thought can only be adequately understood in the light of his critique of Descartes and Cartesianism. I also suggest reasons why Baader's work might well be considered as a source of inspiration for contemporary discussions of postmodernism.